Spanish: between coloniality and poscoloniality: The language and identity binomial (Dissertare, 2019)
The Spanish language was made and makes today a living language between two logics in tension: coloniality and decoloniality. The scientific essay that allows analyzing this relationship, in the light of the language-identity binomial, was intended to reveal how the Spanish language worked as a traditional element of coloniality, since the conquest, making an ontological project effective in Latin America, but in turn It was constituted - by the very nature of this new and new reality - as a decolonizing element that preserved the American substrate and gave the Spanish American real existence through words and the reality symbolized in it. The documentary research modality, with its analytical summary and critical analysis techniques (Montero, Hochman, 2005), was the path selected for the purposes of this work. The contributions of fundamental authors in the field of cultural, philosophical, Latin American and linguistic studies (Dussel, Kusch, Mignolo, Biord Castillo, Quijano, Maldonado-Torres, among others) were combined to combine a conceptual totality that, although it accounts for the coloniality product of the language-culture and identityfusion, also allows to expose it, in the light of the decolonizing processes that today revitalize the language and culture, while still seeing literature as an expression of both.
Keywords: spanish; coloniality; decoloniality